Climate adaptation education: embracing reality or abandoning environmental values - Krasny, Marianne E.; DuBois, Bryce (Environmental Education Research, 2019)
Given the magnitude and immediacy of climate change, how should environmental education (EE) address not only reducing our climate footprint but also climate adaptation? Whereas some approaches to adaptation education are consistent with EE foundational principles, others, while crucial for individual survival, address more immediate risks in ways that do not promote longer-term environmental quality. Using a literature review, we examine issues climate adaptation education raises for the field of EE. We then describe example programs that integrate climate mitigation and adaptation, drawing from EE programs in New York City following devastating floods brought about by Hurricane Sandy. These programs are consistent with a praxis or action research approach to EE where learning is embedded in restoration and other forms of action. We close with reflections on how EE might address climate change adaptation in a manner consistent with climate mitigation education and with our field’s focus on improving environmental quality.
Keywords: Climate change; action research; change; non-formal education; urban and built environment